Analysis Hilmi Ali Yafie's Opinion on Gender Equality in Islamic Education and Its Relevance to Madurese Society: (Literature Review of the Book The Rahima Story) - Siti Farida; Wasik Wasik (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
Gender equality is the equal rights between men and women. Rahima is an organization that fights for this equality through various activities. This study examines the book "The Rahima Story" with two focuses: The concept of gender equality in Islamic education according to Hilmi Ali Yafie. The relevance of the concept to education in Indonesia. The researcher used a qualitative and hermeneutic approach, with content analysis from library sources. The results show that Rahima aims to improve the welfare of women, especially in education equal to men's, through workshops and training. The approach used is andragogy. Rahima believes that men and women have the same rights, creating justice for women through the Human Rights Law and the elimination of domestic violence in Indonesia.